A choke-up grip facilitates faster swing and stride times without compromising bat velocity and bat control - DeRenne, C.; Morgan, C. F.; Escamilla, R. F.; Fleisig, G. S. (The Sport Journal, 2010)
This study investigated the relationship among hitting components and bat control during the normal and choke-up grip swings. Fourteen intercollegiate and professional baseball players were randomly assigned into five hitting groups. Within each group, the following four hitting components were computed to determine the relationship between bat control in two grip conditions (normal; choke-up): (1) Swing time (bat quickness), (2) stride time, (3) bat velocity, and (4) bat-ball contact accuracy. Results indicated significant differences (p =0.01) between choke-up and normal grips in swing time, stride time, and bat velocity. Players using the choke-up grip swing had significant less swing time and stride time than the normal grip swing. Results also indicated significant greater bat velocities (p = 0.01) with normal grip swings than the choke-up grip swings. In addition, further results indicated no significant differences (p = .90) between choke-up and normal grips in bat-ball accuracy. These findings suggest that the choke-up grip facilitates faster swing time and stride time without compromising bat velocity or contact accuracy.